Menggagas Model Pengembangan Manajemen Harta Wakaf Tradisional - Awan Kostrad Diharto (Jurnal Ilmiah Ekonomi Islam, 2019)
Three people issues are: 1) the low quality of education, 2) the cost of increasingly expensive health care, and 3) lack of public welfare, has become a circle of "evil" interrelated and mutually influence one issue among others. Background on the issue tersebutlah, it is necessary that concrete efforts to revisit the idea of classical repertoire, especially Islamic instruments relating to poverty alleviation, one of which is "Waqf". Endowments aims to provide a benefit or benefits diwakafkan property to the person entitled to and used in accordance with teachings of Islamic Sharia. Waqf property in the financing model of traditional, classical fiqh book discusses five models of financing reconstruction waqf property, namely: First, the Loan; Second, Hukr (long-term lease contracts with a lump sum payment that is large enough in advance); Third, Al-Ijaratain (rent with two payments), the Fourth, add the addition of new waqf property and the fifth, onsite replacement (substitution) waqf property. This study develops and implements the fifth above.